Patterns of Increasing Student Motivation and Learning Interest Through Lecturer Competencies at UNISKA Kediri - Siti Aminah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
Kediri Islamic University (UNISKA) Kediri Is a Private Higher Education Institution organized by a Foundation that is composed based on overall science and technology or following Islamic guidance. The campus is a formal educational institution that has the responsibility to continue to educate students by organizing lecture activities as a realization of the vision and mission and goals of education. The method used in this study is classroom action research that is a systematic study of improving the implementation of educational practices by lecturers by taking actions in learning based on their reflection on the results of those actions. This Classroom Action Research uses a quantitative design to collect and analyze data in the form of numbers using the Population Standard Deviation Formula. The data in this study used a questionnaire distributed via Google Forms to the Population Amount. The purpose of this research is to find out the lecturers' competence in Islamic religious subjects towards student learning interest, to find out the increase in student motivation towards learning interest in Islamic religious subjects, to find out positive responses to student questions about lecture material that can link science and Islam in lectures on motivation and learning interest of students of the Faculty of Engineering UNISKA Kediri in FirstÂ Â Semesters of the academic year 2019/2020. Based on the results of a questionnaire with a population of 156 students and 122 respondents, which were tested at less than 75% shows a score of three, which means there needs to be an improvement in improving the competence of religious lecturers and building student motivation and interest in learning.